From chaos to split-ups: SHG microscopy reveals a specific remodelling mechanism in ageing dystrophic muscle - Buttgereit, Andreas; Weber, Cornelia; Garbe, Christoph S.; Friedrich, Oliver (The journal of pathology, 2013)
Duchenne muscular dystrophy (DMD) is a common inherited muscle disease showing chronic inflammation and progressive muscle weakness. Absent dystrophin renders sarcolemma more Ca2+-permeable, disturbs signalling and triggers inflammation. Sustained degeneration/regeneration cycles render muscle cytoarchitecture susceptible to remodelling. Quantitative morphometry was introduced in living cells using second-harmonic generation (SHG) microscopy of myosin. As the time course of cellular remodelling is not known, we used SHG microscopy in mdx muscle fibres over a wide age range for three-dimensional (3D) rendering and detection of verniers and cosine angle sums (CASs). Wild-type (wt) and transgenic mini-dystrophin mice (MinD) were also studied. Vernier densities (VDs) declined in wt and MinD fibres until adulthood, while in mdx fibres, VDs remained significantly elevated during the life span. CAS values were close to unity in adult wt and MinD fibres, in agreement with tight regular myofibril orientation, while always smaller in mdx fibres. Using SHG 3D morphometry, we identified two types of altered ultrastructure: branched fibres and a novel, previously undetected ‘chaotic’ fibre type, both of which can be classified by distinct CAS and VD combinations. We present a novel model of tissue remodelling in dystrophic progression with age that involves the transition from normal to chaotic to branched fibres. Our model predicts a ∼50% contribution of altered cytoarchitecture to progressive force loss with age. We also provide an improved automated image algorithm that is suitable for future ageing studies in human myopathies. Copyright © 2012 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.